2011
DOI: 10.1128/mcb.00903-10
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Signaling through p130Cas Tyrosine Phosphorylation Is Essential for Growth Factor-Dependent Migration of Glioma and Endothelial Cells

Abstract: Neuropilin-1 (NRP1) is a receptor for vascular endothelial growth factor (VEGF) and plays an important role in mediating cell motility. However, the NRP1 signaling pathways important for cell motility are poorly understood. Here we report that p130Cas tyrosine phosphorylation is stimulated by hepatocyte growth factor and platelet-derived growth factor in U87MG glioma cells and VEGF in endothelial cells and is dependent on NRP1 via its intracellular domain. In endothelial cells, NRP1 silencing reduced, but did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
124
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 34 publications
(43 reference statements)
9
124
1
1
Order By: Relevance
“…Of note, a recent study concluded that NRP1 does not localize to focal adhesions, establishing a key difference between these two receptors (Evans et al, 2011). Importantly, we also implicate FAK activation as the prime consequence of VEGF-NRP2 regulation of a6b1 integrin and demonstrate the significance of this mechanism in tumor cells isolated from invasive breast carcinomas.…”
Section: Discussionmentioning
confidence: 56%
“…Of note, a recent study concluded that NRP1 does not localize to focal adhesions, establishing a key difference between these two receptors (Evans et al, 2011). Importantly, we also implicate FAK activation as the prime consequence of VEGF-NRP2 regulation of a6b1 integrin and demonstrate the significance of this mechanism in tumor cells isolated from invasive breast carcinomas.…”
Section: Discussionmentioning
confidence: 56%
“…Enhanced NRP-1 expression during tumorigenesis may represent an angiogenic switch, and the receptor remains an attractive therapeutic target. NRP-1 expression in endothelial and tumor cells has been associated with regulating VEGFR2 trafficking (28)(29)(30)(31). However, the factors that regulate NRP-1 trafficking and the fate of the internalized receptor are less understood.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of more than 60 different mammalian RAB family members (31,35) highlights complex but highly specific functions. While certain RABs are ubiquitously expressed, others demonstrate tissue-or functionspecific expression (32).…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with a previous study that demonstrated NRP1 to be a required component for the regulation of vascular permeability, induced by VEGF (40). Evans et al (44) suggested that treatment of small interfering RNA on NRP1 in HUVEC cells did not affect the phosphorylation of AKT and ERK mediated by VEGF. This was in accordance with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…NRP1 may promote VEGF binding and potentiate VEGFR2 activation and intracellular signaling (44). To illustrate whether NRP1 was involved in the high glucose-induced VEGF autocrine response and occludin reduction, a NRP1 inhibitor, ATWLPPR was administered to RF/6A cells.…”
Section: Discussionmentioning
confidence: 99%